Cocaine-context memories are transcriptionally encoded in nucleus accumbens Arc ensembles - Marine Salery; Arthur Godino; Yu Qing Xu; John F. Fullard; Romain Durand-de Cuttoli; Alexa R. LaBanca; Leanne M. Holt; Scott J. Russo; Panos Roussos; Eric J. Nestler (Nature Communications)
Abstract Learned associations between the rewarding effects of drugs and the context in which they are experienced are critical for context-induced relapse. While context re-exposure triggers the recall of such drug-related associative memories it is unclear whether this relies on the reactivation of and plasticity in neuronal populations previously engaged in their acquisition. Here, using the immediate early gene Arc, we captured a discrete population of nucleus accumbens (NAc) cells activated during the encoding of cocaine-context memory in mice and showed that this neuronal ensemble is later reactivated upon context-induced recall. Furthermore, we show that ensembles recruited at early vs. late stages of memory encoding are largely distinct and contribute differentially to memory retrieval. Single nuclei RNA-sequencing of these ensembles identified plasticity-related transcriptional programs that segregate cocaine-recruited NAc engram-like cells beyond cell-type composition and revealed molecular features unique to distinct stages of memory processing. These findings suggest that activity-dependent transcription upon initial engram allocation further stamps cells for persistent plasticity programs and thereby supports memory traces at the single-cell level. This study also provides insights into the mechanisms supporting pathological memory formation associated with cocaine exposure.